Acute pericarditis: who should stay and who should go?. (25th November 2020) - Ferreira, J; Luis, M; Baptista, R; Monteiro, S; Goncalves, L
Abstract: Background: The European Society of Cardiology (ESC) guidelines for the diagnosis and management of pericardial diseases identify predictive factors of poor prognosis and advise either in favour or against hospitalisation accordingly. Our aim is to evaluate the adequacy of hospitalisation criteria in a cohort of patients presenting to the emergency department (ED) with acute pericarditis. Methods: Retrospective analysis of patients admitted in ED with acute pericarditis, from 2009 to 2019. All patients were evaluated by a cardiologist during ED stay who decided if the patient was to be discharged or hospitalized. Hospitalized and discharged patients were compared regarding primary outcome, defined by a composite of: need for pericardiocentesis and/or cardiac surgery, pericarditis recurrence and all-cause death. Clinical decision was then counterpoised with ESC guidelines. Results: A total of 192 patients were included in the analysis (aged 46±18.5 years-old, 83.3% male) of which 87 (45.5%) were hospitalized. A total of 25% registered the primary outcome, mainly due to acute pericarditis recurrence, occurring in 21.9%. Predictors of recurrence were: glucocorticoid therapy (OR=11.93, 95% CI 3.13–45.5, p<0.001), fever at admission (OR=2.67, 95% CI 1.29–5.49, p=0.008), immunosuppression (OR=4.03, 95% CI 1.280–12.659, p=0.017) and increased cardiothoracic index (OR 3.85, CI 95% 1.67–8.86, p=0.002). Regarding hospitalisation/discharge decision, the ESC guidelines were respected in 72.9% of the cases. However, no significant difference in primary outcome was noted whether the ESC guidelines were respected or not (27.5% vs. 24.3%, p=0.707). Conclusions: Discrepancy between current guidelines and clinical decision did not translate into a different outcome. Funding Acknowledgement: Type of funding source: None